Heterogeneous preferences, market structure and new goods in the Argentinean frozen fried potato industry - González, Julia (2012)
This article studies the preference structure of frozen fried potatoes consumers in Mar del Plata, Argentina, and the effect of changes in market structure and the addition of a new product on prices, market shares, and welfare. Heterogeneity in consumer preferences is found, driven by demographic characteristics. Consumer surplus would decrease with a merger between the two smaller firms of the market, and would increase if the market turned into a single-product firms industry. The results emphasize the importance of both agronomic issues and consumer preferences for the success of the introduction of a credence-attribute in a food industry.